Beyond numbers: a path analysis on how educational ecosystem and math interest spark excellence - Charmaigne A. Eslabra; Roberto G. Sagge Jr.; Dolly Rose F. Temelo; Danilo M. Parreño; Tedric Dave E. Senosa; Peter Ernie D. Paris; Garry C. Cachuela; Sybel Joy F. Labis; Salvador P. Bacio Jr. (Institute of Advanced Engineering and Science, 2026)
Mathematics achievement reflects a web of social, environmental, and motivational forces. This study examined how parental involvement, peer influence, and school support relate to mathematics interest and academic performance among Philippine Science High School (PSHS)–Western Visayas Campus scholars. Using a quantitative descriptive–correlational design, 251 students were selected through proportionate stratified random sampling. Data were collected through Google Forms using the 30-item mathematics interest inventory (MII) (4-point Likert; expert-validated; α=0.899), the 45-item educational ecosystem inventory (EEI) measuring family, peer, and school support (4-point Likert; expert-validated; α=0.910), and official mathematics grades as the achievement indicator. Descriptive statistics and correlation analyses were computed as prerequisites, then relationships were tested through path analysis in a structural equation modeling (SEM) framework, including estimation of direct, indirect, and mediated effects. Results indicated that parental involvement, peer influence, and school support significantly strengthened mathematics interest and were associated with higher mathematics achievement, with the final SEM demonstrating satisfactory model fit. Mathematics interest emerged as a significant mediator, particularly in the link between school support and performance, underscoring interest as a motivational conduit between context and outcomes. Recommendations include strengthening home–school partnerships, institutionalizing peer mentoring, and expanding interest-based pedagogies and opportunities, with continued program evaluation to sustain high performance in science, technology, engineering, and mathematics (STEM)-focused schools.